A Novel Medial Collateral Ligament Reconstruction Procedure Using Semitendinosus Tendon Autograft in Patients With Multiligamentous Knee Injuries: Clinical Outcomes. (June 2013) - Kitamura, Nobuto; Ogawa, Munehiro; Kondo, Eiji; Kitayama, Soichiro; Tohyama, Harukazu; Yasuda, Kazunori
Background: Several new procedures for medial collateral ligament (MCL) reconstruction using a hamstring tendon graft have been reported in the 2000s. However, the midterm and long-term clinical outcomes of these procedures have not been reported. Hypothesis: Postoperative medial stability of the knee that underwent our MCL reconstruction may not be significantly different from that of the noninjured knee. Study Design: Case series; Level of evidence, 4. Methods: A total of 37 patients who sustained multiligamentous knee injuries underwent combined MCL and cruciate ligament reconstruction at our institution between 1994 and 2007. Thirty of the 37 patients were clinically evaluated at least 2 years after surgery. Sixteen had combined MCL and anterior cruciate ligament (ACL) reconstruction, 5 had combined MCL and posterior cruciate ligament (PCL) reconstruction, and 9 had combined MCL, ACL, and PCL reconstruction. The International Knee Documentation Committee (IKDC) evaluation form and Lysholm score were used to evaluate postoperative knee function. Anteroposterior knee laxity was examined with a KT-2000 arthrometer. To assess objective medial instability, we performed a stress radiograph examination under valgus stress with the knee at 20° of flexion. Results: At the final follow-up, 1 patient showed a loss of knee extension of more than 3°. Five patients revealed a loss of knee flexion of 6° to 15° and 2 patients of 16° to 25°. Lysholm scores averaged 94.8 points. In the IKDC evaluation, 9 patients were graded as A, 17 were graded as B, 3 were graded as C, and 1 was graded as D. In the stress radiograph examination, the mean medial joint opening was 8.5 ± 1.6 mm in the reconstructed knee and 8.0 ± 1.2 mm in the healthy opposite knee. There was no significant difference in the medial joint opening between reconstructed and intact knees. Conclusion: Medial collateral ligament reconstruction for chronic combined knee instabilities can be safely performed using hamstring tendon autografts, and the clinical outcome with a minimum 2-year follow-up was favorable with satisfactory stability.